Hubungan Job Insecurity terhadap Intensi Turnover pada Karyawan Outsourcing - Monica Florida Johan; Rizal Nopriyanto; Nurul Ismi Ainun (Psyche 165 Journal, 2020)
This study aims to determine the relationship between job insecurity andintention turnover inemployees outsourcing. The sample in this study wasemployees outsourcing at X Yogyakarta University, totaling 50 people. Data collection was carried out by distributing 2 scales, namely the intention scale turnover(alpha 0.894) and job insecurity (alpha 0.737). The analysis technique used is the product moment withprogram SPSS 19 for windows. The analysis showed that job insecurity onintention turnover was 0.239 with p = 0.047 (<0.05) . It was concluded that job insecurity is related tointention turnover.